2014
DOI: 10.1111/jph.12267
|View full text |Cite
|
Sign up to set email alerts
|

NTPDase Specific Inhibitors Suppress Rice Infection by Magnaporthe oryzae

Abstract: Evolutionarily conserved ecto-nucleoside triphosphate diphosphohydrolases (referred to 'NTPDases' below) are important ecto-nucleotidases that are able to hydrolyse NTPs and NDPs in the environment to the monophosphate form. NTPDases are found in a variety of eukaryotic organisms including medical pathogens. However, pathogenic roles of these NTPDases in medical and plant pathogens are still very obscure. Here, we demonstrate that conidial germination, appressorium formation and pathogenicity of rice blast fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…S2), just as, by themselves, they do not inhibit the growth of plants at concentrations that increase herbicide effectiveness. In contrast, pretreatment of the rice blast fungus, Magnaporthe oryzae, with anti-psychotic drugs that can inhibit ecto-NTPDases (ecto-apyrases) does suppress the effectiveness of this fungus in infecting rice (Long et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…S2), just as, by themselves, they do not inhibit the growth of plants at concentrations that increase herbicide effectiveness. In contrast, pretreatment of the rice blast fungus, Magnaporthe oryzae, with anti-psychotic drugs that can inhibit ecto-NTPDases (ecto-apyrases) does suppress the effectiveness of this fungus in infecting rice (Long et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…For M. oryzae inoculation, compatible and incompatible rice cultivars (Lijiangxintuanheigu and CO39 respectively) were used for the pathogenicity assay. Detached rice leaves (at 3-to 4-leaf stage, intact or wounded on the surface) were inoculated by dropping M. oryzae conidial suspension (5 3 10 5 conidia/ml, 5 ll) on the leaf surface; pathogenicity assay were performed as our previously described methods (Long et al, 2015).…”
Section: Plant Infection Experimentsmentioning
confidence: 99%
“…Given that extracellular ATP was shown to be involved in cytolysis, cell adhesion, and growth of various microbes ( Roberto Meyer-Fernandes, 2002 ; Meyer-Fernandes et al, 2004 ; Li et al, 2011 ), these pathogenic microbes may be merely protecting themselves from ATP, a very reactive molecule. Correspondingly, a recent report by Long et al (2014) demonstrated that conidial germination, appressorium formation and pathogenicity of rice blast fungus Magnaporthe oryzae were significantly reduced by pretreatment with nucleotidase-specific inhibitors.…”
Section: Role Of Extracellular Atp As a Dampmentioning
confidence: 83%